Advances in native high‐performance liquid chromatography and intact mass spectrometry for the characterization of biopharmaceutical products. Issue 1 (2nd November 2017) - Tassi, Marco; De Vos, Jelle; Chatterjee, Sneha; Sobott, Frank; Bones, Jonathan; Eeltink, Sebastiaan
Abstract: The characterization of biotherapeutics represents a major analytical challenge. This review discusses the current state‐of‐the‐art in analytical technologies to profile biopharma products under native conditions, i.e., the protein three dimensional conformation is maintained during liquid chromatographic analysis. Native liquid‐chromatographic modes that are discussed include aqueous size‐exclusion chromatography, hydrophobic interaction chromatography, and ion‐exchange chromatography. Infusion conditions and the possibilities and limitations to hyphenate native liquid chromatography to mass spectrometry are discussed. Furthermore, the applicability of native liquid‐chromatography methods and intact mass spectrometry analysis for the characterization of monoclonal antibodies and antibody–drug conjugates is discussed.